2001
DOI: 10.1128/aem.67.10.4805-4816.2001
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Functional Analysis of the tbc Operons for Catabolism of Alkyl- and Chloroaromatic Compounds in Burkholderia sp. Strain JS150

Abstract: Burkholderia sp. strain JS150 is able to metabolize a wide range of alkyl-and chloroaromatic hydrocarbons through multiple, apparently redundant catabolic pathways. Previous research has shown that strain JS150 is able to synthesize enzymes for multiple upper pathways as well as multiple lower pathways to accommodate variously substituted catechols that result from degradation of complex mixtures of monoaromatic compounds. We report here the genetic organization and functional characterization of a gene cluste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 67 publications
1
23
0
1
Order By: Relevance
“…Johnson and Olsen (22) have previously shown that the tbm operon from strain JS150 has the same gene arrangement and strong sequence identity to the phenol hydroxylases encoded by the dmp, phe, and phh genes of strains CF600, BH, and P35X, respectively. Moreover, tbmD is also responsible for oxidation of o-cresol produced from the initial hydroxylation of toluene, supporting the association of this family with oxidation of hydroxylated substrates (23). Members of the R.2 and R.3 families will oxidize hydroxylated intermediates in addition to toluene (touA).…”
Section: Resultsmentioning
confidence: 99%
“…Johnson and Olsen (22) have previously shown that the tbm operon from strain JS150 has the same gene arrangement and strong sequence identity to the phenol hydroxylases encoded by the dmp, phe, and phh genes of strains CF600, BH, and P35X, respectively. Moreover, tbmD is also responsible for oxidation of o-cresol produced from the initial hydroxylation of toluene, supporting the association of this family with oxidation of hydroxylated substrates (23). Members of the R.2 and R.3 families will oxidize hydroxylated intermediates in addition to toluene (touA).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, PH is more restricted in its regioselectivity than ToMO, but it is more relaxed than other group 1 BMMs, like T2MO, which produce only o-cresol (16,17,24).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the sequences from nucleotide and protein databases indicates that most bacterial strains possess only one BMM, but a few cases (3 out of 31) of bacterial genomes coding for more than one monooxygenase have been found (21). Two group 1 (phenol hydroxylases) and one group 2 (toluene-benzene monooxygenases) BMMs have been found in the genome of Ralstonia metallidurans CH34 (21), and three BMMs belonging to groups 1 and 2 were detected in Burkholderia cepacia (formerly Pseudomonas cepacia) JS150 (16,21). B. cepacia JS150 instead is endowed with the ability to use different pathways for the metabolism of substituted aromatic compounds (16).…”
mentioning
confidence: 99%
“…Two group 1 (phenol hydroxylases) and one group 2 (toluene-benzene monooxygenases) BMMs have been found in the genome of Ralstonia metallidurans CH34 (21), and three BMMs belonging to groups 1 and 2 were detected in Burkholderia cepacia (formerly Pseudomonas cepacia) JS150 (16,21). B. cepacia JS150 instead is endowed with the ability to use different pathways for the metabolism of substituted aromatic compounds (16). This led to the suggestion that in B. cepacia JS150, toluene metabolism is initiated by one dioxygenase and two distinct BMMs with different specificities (a toluene 4-monooxygenase [T4MO] belonging to group 2 and a toluene 2-monooxygenase [T2MO] belonging to group 1), whereas a third BMM acts downstream of the other two monooxygenases (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation